PENGERTIAN, HUBUNGAN, DAN IMPLEMENTASI SOFT SKILLS, PEMBELAJARAN AFEKTIF, DAN PENDIDIKAN KARAKTER DALAM PROSES BELAJAR MENGAJAR - Suganda, Dadang (LP2M ISBI Bandung, 2017)
This paper is the result of the author who has participated in various trainings organized by the Director General of Higher Education, Ministry of National Education. Based on that, it can be stated that both soft skills, effective learning, and character education, the three are not in the realm related to technical skills, professional scientific fields, or things that are motoric in nature. All three are in the area ofpersonality competence. All three are more closely related to EQ., SQ., Heart, to live together and to be than with IQ, hand, head, to do, or to know. Thus the meaning of sofs skills, character education is not much diferent from affective abilities. However, of course there are diferences, such as the sofs skill gives a broader picture ofpersonality, while character education provides a more specific and specific personality picture than affective competence. This can be seen clearly from the many and broad scope of the attributes of soft skills, as well as the specific and specific character education goals that emphasize the basic values of character, namely honesty, smart, tough, and caring. Efforts to carry out character education in the ISBI Bandung environment will be confronted with the main problem, namely the ability to make changes in the level of thought patterns and patterns of action. The mindset of entering into the realm, namely the implementation of activities carried out in the ISBI Bandung environment must be able to incorporate elements of the basic values of character into each activity carried out. The pattern of action can be in the form of building synergy between lecturers and students. The synergy between lecturers and students is an intellectual capital to realize success..